Multiplanar Fourier-transform phase-shifting digital holography with a generalized Fibonacci lens. (3rd April 2019) - Zhang, Yingge; Yang, Pengqian; Tian, Ailing; Liu, Bingcai; Zhang, Junyong
Abstract: Phase-shifting interference is an important technology for optical phase measurement. Generalized Fibonacci sieves can generate several equal-intensity diffraction-limited foci on axis. Here we propose multiplanar Fourier-transform phase-shifting digital holography. A test sample, fabricated on a chrome plate, is located in the front focal plane of the multi-focal lens. In the back focal plane, the interference patterns are recorded by detector arrays. The experimental results agree well with our theory. Owing to the advantages of small volume, little weight and easy processing, these kinds of diffractive lenses have great potential in array imaging, x-ray holography and microscopy for biological cells.